AKIBAT HUKUM PENGANGKATAN ANAK TANPA PENETAPAN PENGADILAN - Rini Safarianingsih (Universitas Kapuas Sintang, 2021)
An adopted child defines as a child’s rights are transferred from original parents, legal guardian, or other people who are responsible for the care, education, and nurturing of the child, into adoptive parents based on a decision or court order, as regulated in Article 1 Number 1 Government Regulation No. 54 of 2007 about the Implementation of Child Adoption.Children adoptions apply for both married couples and women or men who are single as long as they have a highly motivated to raise a child. In the process adoption, the prospective adoptive parents need a statement from the parents when handing over the child. Adoption of children hasbecome a practice among Indonesian people and has been taken up by religious and non-Islamic state judiciaries. Adoption does not break the blood relationship between the adopted child and his or her born parent. Section 6 (1) states that adoptive parents are obliged to notify the adoptive child of the birth and birth parent, and Section 6(2) takes into account the motivation of the child in question for birth and birth parent notification. moreover, adoption of a child is considered valid if a court decision is made and entered into the registry documents.